Impact of universal health coverage on childhood cancer outcomes in Indonesia. Issue 9 (11th June 2021) - Indraswari, Braghmandita Widya; Kelling, Emil; Vassileva, Sofi M.; Sitaresmi, Mei Neni; Danardono, Danardono; Mulatsih, Sri; Supriyadi, Eddy; Widjajanto, Pudjo Hagung; Sutaryo, Sutaryo; Kaspers, Gertjan L.; Mostert, Saskia
Abstract: Background: Starting from 2014, the Indonesian government has implemented Universal Health Coverage (UHC) with the aim to make healthcare services accessible and affordable to all Indonesian citizens. A major reason for childhood cancer treatment failure in low‐ and middle‐income countries, particularly among families with low socioeconomic status (SES), is abandonment of expensive cancer treatment. Our study compared childhood cancer treatment outcomes of the overall, low, and high SES population before and after introduction of UHC at a large Indonesian academic hospital. Methods: Medical records of 1040 patients diagnosed with childhood cancer before (2011‐2013, n = 506) and after (2014‐2016, n = 534) introduction of UHC were abstracted retrospectively. Data on treatment outcome, SES, and health‐insurance status at diagnosis were obtained. Findings: After introduction of UHC, the number of insured patients increased from 38% to 82% ( P < 0.001). Among low SES population, insurance coverage increased from 40% to 85% ( P < 0.001), and among high SES population from 33% to 77% ( P < 0.001). In the overall population, treatment abandonment decreased from 36% to 22% ( P < 0.001). Event‐free survival estimates at four years after diagnosis of overall population improved from 16% to 22% ( P < 0.001). Hazard ratio for treatment failure was 1.26 (CI: 1.07‐1.48, P = 0.006) for uninsured versus insured patients. In the low SES population, treatment abandonment decreased from 36% to 19% ( P < 0.001). Event‐free survival estimates at four years after diagnosis of low SES population improved from 14% to 22% ( P < 0.001). Interpretation: Introduction of UHC in Indonesia contributed significantly to better treatment outcome and event‐free survival of children with cancer from low SES families.